Monitoring Automatic Color Walln Paint With Blynk Application - Sutono, Sutono (Indonesian Journal of Engineering Research, 2023)
Painting is a process of giving color to an object's surface which aims to beautify, strengthen and protect the object. Today, the need for paint continues to increase with the demand for various colors, generally sellers or painters mix several primary paint colors to produce a variety of colors. In practice, many of them still use the manual method, this is considered less efficient and less practical. This research produces an Automatic Primary Color Wall Paint Mixing System Using the TCS34725 Sensor. The paint pigments used in this system are red, green and blue pigments. The TCS34725 sensor is used as a color detector for reference objects with red, green and blue data formats. The results from the TCS34725 sensor readings are then processed by the NodeMCU8266 microcontroller to control the water pump to issue bubble pigmentation for wall paint based on the PWM value or color code with a time lag of every 100 milliseconds of bubble. Next, mixing the primary color pigments for wall paint and white wall paint will be stirred using a 12VDC motor until all the primary color pigments and white wall paint are evenly mixed. Furthermore, the TCS34725 sensor is reused to check the results of the mixing of the primary color pigments for wall paint and white wall paint. The results of this study note that the TCS34725 sensor can be used as a paint color detector by looking for the RGB value on the color card. From the results of the water pump test, the accuracy value for the red water pump is 62.21%, the green water pump is 65.28% and the blue water pump is 61.29%. From the results of the mixing obtained an average accuracy of 62.93% by taking sample data as much as 10 times mixing the primary color pigment with white wall paint.Kata kunci: Node MCU8266, RGB, Cat tembok, PWM, Warna primer, Water pump, TCS34725, Bubble, Pikmen color.